Risk factors for adverse maternal and perinatal outcomes in women with preeclampsia: analysis of 1396 cases. Issue 6 (30th April 2018) - Li, Xun; Zhang, Weishe; Lin, Jianhua; Liu, Huai; Yang, Zujing; Teng, Yincheng; Duan, Si; Lin, Xinxiu; Xie, Yingming; Li, Yuanqiu; Xie, Liangqun; Peng, Qiaozhen; et al.
Abstract : Preeclampsia is a major cause of adverse maternal and perinatal outcomes, but how to identify women and fetuses at increased risk for later adverse events is a challenge. This study aimed to investigate the risk factors for adverse maternal and perinatal outcomes in women with preeclampsia. Data from 1396 women with preeclampsia were retrospectively collected and analyzed. Eighteen candidate risk factors and 12 adverse outcomes were investigated. The following factors were found to be significantly associated with at least one adverse outcome: maternal age 35 years or older, multiple birth, the usage of assisted reproductive technology, living in a rural area, history of pregnancy‐induced hypertension, male fetus, multigravida, or having polycystic ovary syndrome, hemolysis, elevated liver enzymes, and low platelet count syndrome, intrahepatic cholestasis of pregnancy, cardiovascular disease, gestational diabetes mellitus, systemic lupus erythematosus, thyroid disease, or liver disease. Compared with patients without any identified risk factors, patients with preeclampsia with three or more risk factors were at increased risk for severe adverse outcomes. Those findings demonstrated that maternal risk factors could be used as indicators supplementary to clinical symptoms and laboratory test results for the risk assessment in women with preeclampsia.